STRATEGI BERSAING PADA GELATIK RESIDENCE PALU - Tanwir D G Djuma; Johnny Tanamal; Syamsul Bachri Daeng Parani (Jurnal Ilmu Manajemen Universitas Tadulako (JIMUT), 2015)
PT. Regional Trypillian is a company that is engaged in the development of new houses to prosper the  society,  especially  by  providing  residence and  develop  its  role  in  economic  development  in marketing  the residential  products  and  utilization  of  manpower. The  establishment of  the  company initiated by Mr. Sofyan Hudri since February 15, 2014, starting from an attempt to manage, market, and produce home with investors/landowners. Wren's housing residence consists of 2 types: type 50 and type 90. The purpose of this study is to determine competition faced by Wren Residence in Palu and  to examine  alternative  strategies that can  be  used  by  Wren  Residence.  Data  analysis  technique used is the SWOT analysis (Strength, Weakness, Opportunity, Threat). Based on the results of SWOT analysis  in  the  form  of  matrix  diagram  and  IE table,  it  finds  that  competitive  strategies  of  Wren Residence  is focused  on  aggressive  strategy  (growth-oriented  strategy)  that  is suitable  with  the existing opportunities. PT. Regional Trypillian adalah perusahaan yang bergerak dalam pengembangan rumah baru untuk mencapai  kesejahteraan  masyarakat, terutama  dengan  menyediakan  tempat  tinggal  dan mengembangkan perannya  dalam  pembangunan  ekonomi dalam  memasarkan  produk hunian  dan pemanfaatan tenaga kerja. Pembentukan perusahaan yang diprakarsai oleh Bapak Sofyan Hudri sejak 15  Februari  2014  ini,  mulai dari  usaha  mengelola,  memasarkan,  dan  menghasilkan  rumah dengan investor  /  pemilik  lahan.  Tempat tinggal  Wren  terdiri  dari  2 tipe:  tipe  50  dan  tipe  90.  Tujuan  dari penelitian  ini  adalah  untuk mengetahui  kompetisi  yang  dihadapi Wren  Residence  di  Palu  dan untuk mengkaji  strategi  alternatif  yang  dapat  digunakan  oleh  Wren Residence.  Teknik  analisis  data  yang digunakan  adalah  analisis SWOT  (Strength,  Weakness,  Opportunity,  Threat).  Berdasarkan  hasil analisis  SWOT  berupa  diagram  matriks  dan  tabel  IE,  maka  strategi  kompetitif  Wren  Residence difokuskan pada strategi agresif (strategi berorientasi pertumbuhan) yang sesuai dengan peluang yang ada.